The Role of Mtor Inhibitors in Endocrine Resistance Therapy of Breast Cancer Type ER+ - Syarinta Adenina; Bantari Wisynu Kusuma Wardhani (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Breast cancer is the leading cause of death in women. Although hormonal therapy has produced positive results in HR+ breast cancer, resistance to this therapy remains a challenge in the treatment of breast cancer. Various mechanisms have been proposed as an explanation of resistance in breast cancer, one of which is the activation of the PI3K/AKT/mTOR pathway. The PI3K/AKT/mTOR pathway is a transduction pathway that regulates many important aspects in both normal cells and cancer cells, including cell proliferation, apoptosis, cell morphology and migration, protein synthesis, and integrase metabolism. Preclinical dan clinical data show inhibition of this pathway can improve survival, especially in resistant hormonal therapy models. The use of mTOR inhibitors (everolismus) has been approved by the FDA as a combination therapy with exemestane for postmenopausal women with HR+/HER2-breast cancer.